Sharia-Based Human Capital Development: A Literature Review on Character Building For Islamic Banking Competitiveness - Ashari, Denny Rakhmad Widi; Hidayati, Atina; Al Haris, Mohammad Basid; Pambudi, Setyoadi; Waskita, Gautama Sastra (Jurnal At-Tamwil: Kajian Ekonomi Syariah, 2025)
Purpose – This study aims to examine the integration of Sharia values in human resource character building within Islamic banking institutions. The research highlights the importance of developing Islamic character-based human capital as a strategic foundation for achieving sustainable competitiveness in the Islamic banking industry. The study is motivated by the increasing need to align human resource strategies with Sharia principles to ensure both compliance and differentiation in the financial sector. Methods – The research uses a qualitative approach using a literature review of academic articles, reports, and policy documents published in the last decade. Content analysis was conducted to identify recurring themes, conceptual frameworks, and strategic implications of Sharia-based human capital development. Findings – The study reveals that Islamic character building, rooted in Sharia values such as Shiddiq, Amanah, Tabligh, and Fathanah, has a significant contribution to the development of trustworthy, competent, and value-driven employees. These values foster customer trust, strengthen organizational culture, and enhance the competitive advantage of Islamic banks. However, challenges remain in terms of practical implementation, organizational commitment, and balancing technical competencies with ethical-spiritual development. Research Limitations – As a literature-based study, the findings are conceptual and may not fully capture empirical variations across different Islamic banking institutions. Future research should include case studies or empirical validation to test the applicability of the proposed framework in diverse contexts. Value – This study contributes to the field of Applied Islamic Finance by providing a conceptual framework that links Sharia-based human capital development with sustainable competitiveness in Islamic banking. It highlights the strategic role of Islamic character building as a differentiating factor that cannot be easily replicated by conventional banks.